Biological, ecological, conservation and legal information for all species and subspecies of Australian bird - Garnett, Stephen T.; Duursma, Daisy E.; Ehmke, Glenn; Guay, Patrick-Jean; Stewart, Alistair; Szabo, Judit K.; Weston, Michael A.; Bennett, Simon; Crowley, Gabriel M.; Drynan, David; Dutson, Guy; Fitzherbert, Kate; et al. (Scientific data, 2015)
We introduce a dataset of biological, ecological, conservation and legal information for every species and subspecies of Australian bird, 2056 taxa or populations in total. Version 1 contains 230 fields grouped under the following headings: Taxonomy & nomenclature, Phylogeny, Australian population status, Conservation status, Legal status, Distribution, Morphology, Habitat, Food, Behaviour, Breeding, Mobility and Climate metrics. It is envisaged that the dataset will be updated periodically with new data for existing fields and the addition of new fields. The dataset has already had, and will continue to have applications in Australian and international ornithology, especially those that require standard information for a large number of taxa. Design Type(s) data integration objective • database creation objective Measurement Type(s) ornithology Technology Type(s) digital curation Factor Type(s) Sample Characteristic(s) Struthio • Casuarius • Dromaius • Anseranas • Dendrocygna • Oxyura • Malacorhynchus • Cereopsis • Cygnus • Branta • Radjah • Tadorna • Aythya • Spatula • Mareca • Anas • Stictonetta • Biziura • Chenonetta • Nettapus • Alectura • Leipoa • Megapodius • Numida • Callipepla • Pavo • Coturnix • Synoicus • Gallus • Phasianus • Meleagris • Phoenicopterus • Tachybaptus • Poliocephalus • Podiceps • Columba • Streptopelia • Macropygia • Leucosarcia • Petrophassa • Geophaps • Phaps • Ocyphaps • Geopelia • Chalcophaps • Ducula • Ptilinopus • Hemiphaga • Lopholaimus • Centropus • Eudynamys • Urodynamys • Scythrops • Chalcites • Cacomantis • Heteroscenes • Hierococcyx • Cuculus • Ardeotis • Podargus • Eurostopodus • Caprimulgus • Aegotheles • Mearnsia • Hirundapus • Collocalia • Aerodramus • Apus • Rallina • Lewinia • Eulabeornis • Hypotaenidia • Crex • Porzana • Zapornia • Amaurornis • Gallicrex • Porphyrio • Gallinula • Tribonyx • Fulica • Antigone • Burhinus • Esacus • Chionis • Haematopus • Cladorhynchus • Recurvirostra • Himantopus • Pluvialis • Charadrius • Thinornis • Elseyornis • Vanellus • Erythrogonys • Pedionomus • Rostratula • Hydrophasianus • Irediparra • Bartramia • Numenius • Limosa • Arenaria • Calidris • Limnodromus • Gallinago • Xenus • Actitis • Tringa • Steganopus • Phalaropus • Turnix • Stiltia • Glareola • Stercorarius • Catharacta • Anous • Procelsterna • Gygis • Xema • Chroicocephalus • Leucophaeus • Larus • Onychoprion • Sternula • Gelochelidon • Hydroprogne • Chlidonias • Sterna • Thalasseus • Phaethon • Aptenodytes • Pygoscelis • Eudyptes • Eudyptula • Spheniscus • Oceanites • Garrodia • Pelagodroma • Fregetta • Nesofregetta • Phoebastria • Diomedea • Phoebetria • Thalassarche • Hydrobates • Macronectes • Fulmarus • Thalassoica • Daption • Pagodroma • Halobaena • Pachyptila • Aphrodroma • Pterodroma • Procellaria • Ardenna • Calonectris • Puffinus • Pseudobulweria • Bulweria • Pelecanoides • Ephippiorhynchus • Pelecanus • Botaurus • Ixobrychus • Gorsachius • Nycticorax • Butorides • Ardeola • Bubulcus • Ardea • Egretta • Threskiornis • Platalea • Plegadis • Fregata • Papasula • Morus • Sula • Microcarbo • Phalacrocorax • Anhinga • Pandion • Elanus • Pernis • Hamirostra • Lophoictinia • Aviceda • Aquila • Hieraaetus • Circus • Accipiter • Erythrotriorchis • Haliaeetus • Haliastur • Milvus • Tyto • Ninox • Otis • Ketupa • Upupa • Merops • Eurystomus • Coracias • Ceyx • Alcedo • Halcyon • Syma • Todiramphus • Tanysiptera • Dacelo • Falco • Nestor • Nymphicus • Calyptorhynchus • Zanda • Probosciger • Callocephalon • Eolophus • Cacatua • Polytelis • Alisterus • Aprosmictus • Eclectus • Geoffroyus • Psephotus • Northiella • Psephotellus • Purpureicephalus • Platycercus • Barnardius • Lathamus • Cyanoramphus • Pezoporus • Neopsephotus • Neophema • Glossopsitta • Psitteuteles • Trichoglossus • Melopsittacus • Cyclopsitta • Pitta • Menura • Atrichornis • Ailuroedus • Scenopoeetes • Amblyornis • Sericulus • Ptilonorhynchus • Cormobates • Climacteris • Malurus • Stipiturus • Amytornis • Dasyornis • Sugomel • Myzomela • Grantiella • Plectorhyncha • Xanthotis • Philemon • Cissomela • Lichmera • Trichodere • Phylidonyris • Nesoptilotis • Entomyzon • Melithreptus • Glyciphila • Glycichaera • Acanthorhynchus • Certhionyx • Conopophila • Ramsayornis • Ashbyia • Epthianura • Stomiopera • Meliphaga • Acanthagenys • Anthochaera • Bolemoreus • Gavicalis • Ptilotula • Purnella • Caligavis • Lichenostomus • Manorina • Pardalotus • Oreoscopus • Gerygone • Smicrornis • Pycnoptilus • Pyrrholaemus • Calamanthus • Origma • Sericornis • Acanthornis • Aphelocephala • Acanthiza • Orthonyx • Pomatostomus • Daphoenositta • Coracina • Edolisoma • Lalage • Cinclosoma • Pachycephala • Colluricincla • Falcunculus • Oreoica • Psophodes • Sphecotheres • Oriolus • Machaerirhynchus • Strepera • Melloria • Gymnorhina • Cracticus • Artamus • Dicrurus • Rhipidura • Lanius • Pica • Corvus • Myiagra • Arses • Grallina • Symposiarchus • Carterornis • Monarcha • Corcorax • Struthidea • Phonygammus • Lophorina • Petroica • Kempiella • Microeca • Drymodes • Poecilodryas • Heteromyias • Eopsaltria • Quoyornis • Tregellasia • Melanodryas • Peneothello • Dicaeum • Cinnyris • Lonchura • Heteromunia • Stagonopleura • Emblema • Neochmia • Poephila • Taeniopygia • Erythrura • Chloebia • Passer • Dendronanthus • Anthus • Motacilla • Fringilla • Emberiza • Chloris • Acanthis • Carduelis • Mirafra • Alauda • Cisticola • Locustella • Cincloramphus • Poodytes • Acrocephalus • Cheramoeca • Delichon • Petrochelidon • Cecropis • Hirundo • Pycnonotus • Phylloscopus • Sericercus • Zosterops • Sturnus • Pastor • Agrospar • Acridotheres • Aplonis • Muscicapa • Cyanoptila • Ficedula • Monticola • Luscinia • Oenanthe • Zoothera • Geokichla • Turdus • Anser • Cairina • Alectoris • Gallicolumba • Caloenas • Gallirallus • Leucocarbo • Butastur • Psittacula • Ploceus • Euplectes • Australia Machine-accessible metadata file describing the reported data (ISA-Tab format)